Fear of Ebola Epidemics in Bangladesh: Issues and Approaches - Rabiul, Ahasan (2014)
The Ebola virus is the cause of a viral hemorrhagic fe-ver (e.g. figure below shows the incubation period and courses of acute illness syndrome) currently killing peo-ple in West Africa.' Bengali speaking people currently are living in the affected region including hundreds of military peacekeepers from Bangladesh. BGMEA is dealing with taking orders and shipments of garments in Africa.' There are business people and Bangladeshi farmers leasing agricultural lands in some parts of Af-rica.34 It is thus imperative that the virus might travel to Bangladesh through our peacekeepers or others cur-rently working and living in various parts of Africa in-cluding Congo, Liberia, Guinea, and Sierra Leone. The deadly virus could spread at an alarming rate unless emergency steps are seriously taken to contain and stop it